Efeito da dexmedetomidina ou do remifentanil na função renal de pacientes submetidos à cirúrgia bariátrica - Meinberg, Antonio Carlos (2008)
The objective of the present research was to study the comparative effects of dexmedetomidine and remifentanil on the renal function of morbidly obese patients submitted to bariatric surgery. Casuistic and Method: After approval by the local Ethics Council, in the period from August 2004 to August 2005, 61 patients were studied prospectively independent of race; ages ranged from 19 to 63 years (35.6 Â± 9.9 years); 17 (27.8%) were males and 44 (72.2%) female. The individuals were divided randomly into two groups: remifentanil (group R = 0,1 Âµg.kg-1.min-1) and dexmedetomidine (group D = 1 ug.kg-1 during 10 min and after 0,5 ug.kg-1.h-1). Isoflurane was used to maintenance BIS around 50 in both groups. The study monitored hemodynamic and ventilatory parameters and anesthesia depth. Renal function was evaluated at moments in each of three phases: before anesthesia (M0), after anesthetic induction (M1) and after surgical incision (M2). Plasma concentrations were determined for glucose, antidiuretic hormone, creatinine, urea, sodium, potassium and osmolarity and urinary concentrations for creatinine, urea, sodium, potassium and osmolarity. Results: The plasma concentration values of sodium, creatinine, urea and antidiuretic hormone at MO, M1 and M2 did not present differences between groups R and D. Significant differences were found between groups for potassium at M1 (p < 0.05), osmolarity at M2 (p < 0.05) and glucose at M1 and M2 (p < 0.01 and p < 0.001, respectively). The urinary volume was significantly different between groups only at moment M2 (p < 0.001). Mean clearance values did not present significant difference between groups at M0. At the moment M1, the differences were significant between groups for potassium (p < 0.001), creatinine (p < 0.05) and urea (p < 0.01). At M2 there was a difference between groups only for potassium and urea (p < 0.05 in both). In group R there was a drop in mean clearance values from M0 to M1 for sodium, potassium, urea, creatinine and osmolarity; in group D the mean clearance values of sodium and osmolarity rose while values for potassium, creatinine and urea fell. There was a reduction in both groups for all variables between moments M1 and M2 and from M0 to M2. Conclusions: In both groups, the clearance values fell from moments M0 to M2. This result indicates that renal function of obese patients submitted to bariatric surgery presented a physiological response compatible with the effect of anesthetic-surgical stress. In group R, all clearances were reduced at M1, indicating a response compatible with anesthetic-surgical stress. In the dexmedetomidine group (D), creatinine and sodium clearances were elevated at M1. Urinary volume was greater at M2. These results are suggestive of better preservation of renal function.